Is Cooperative Memory Special? The Role of Costly Errors, Context, and Social Network Size When Remembering Cooperative Actions - Winke, Tim; Stevens, Jeffrey R. (Frontiers in Robotics and AI, 2017)
Theoretical studies of cooperative behavior have focused on decision strategies, such as tit-for-tat, that depend on remembering a partner's last choices. Yet, an empirical study by Stevens, Volstorf, Schooler, and Rieskamp (2011) demonstrated that human memory may not meet the requirements needed to use these strategies. When asked to recall the previous behavior of simulated partners in a cooperative memory task, participants performed poorly, making errors in 10–24% of the trials. However, we do not know the extent to which this task taps specialized cognition for cooperation. It may be possible to engage participants in more cooperative, strategic thinking, which may improve memory. On the other hand, compared to other situations, a cooperative context may already engage improved memory via cheater detection mechanisms. The current study investigated the specificity of memory in cooperative contexts by varying (1) the costs of errors in memory by making forgetting defection more costly and (2) whether the recall situation is framed as a cooperative or neutral context. Also, we investigated whether variation in participants' social network size could account for individual differences observed in memory accuracy. We found that neither including differential costs for misremembering defection nor removing the cooperative context influenced memory accuracy for cooperation. Combined, these results suggest that memory accuracy is robust to differences in the cooperative context: Adding more strategic components does not help accuracy and removing cooperative components does not hurt accuracy. Social network size, however, did correlate with memory accuracy: People with larger networks remembered events better. These findings suggest that cooperative memory does not seem to be special compared to other forms of memory, which aligns with previous work demonstrating the domain generality of memory. However, the demands of interacting in a large social network may require excellent memory. Thus, modeling the evolution of cooperation requires an understanding of both the social environment in which agents interact, as well as the cognitive capabilities of these agents.